I'll Tell You What : The Life of Elizabeth Inchbald - Jenkins, Annibel (Book collections on Project MUSE., 2015)
Elizabeth Simpson Inchbald (1753--1821) was one of the leading literary figures of the late eighteenth century -- an actress, a successful playwright and editor of several collections of plays, a popular novelist, and a drama critic. Considered a beautiful, independent woman, Inchbald was much involved in the theatrical, literary, and publishing life of London. Elizabeth Simpson ran away from home at age eighteen to seek fame as an actress in London and quickly married Joseph Inchbald, an actor twice her age. They toured the stage together until his sudden death in 1779. She made her London sta.